Smart Community System for PPKJ Residential with notification (SmartHome) / Muhammad Alif Umar Abdullah - Abdullah, Muhammad Alif Umar (2020)
The residential management system is now one of the most significant tools to manage the residential area. It is mostly used to the related activities such as payment fees, facilities booking, announcement & news, and issue the complaint. The study area for this project is in PPKJ residential, Seksyen 8, Bandar Baru Bangi. Currently, this residential is operating manually for certain activities such as log book to record all the payment fees, provide form for home away form as well as improper way to issue the complaint. They do not have sufficient software to manage their activities. It requires a committee to wait on the guard house to collect the payment for every month. Other than that, committee need to distribute the home away from when festive session coming or resident need to pick up by itself. Besides that, when resident need to issue the complaint, they need to meet the committee, make a call or WhatsApp. To decrease these issues, a mobile application system is created to help speed up the operations. To develop a Smart Home mobile application for PPKJ residential with notification by providing a home away and complaint platform for the residents. This project is intended to solve all the difficulties relating to the operations and to enhance the precision, security, and effectiveness operations. The system was developed using four out of six waterfall methodology stages which are planning, requirements analysis, design and implementation. In the first stage, the interview session was performed to collect data. Second stage is requirement analysis, all the requirements and related diagram in this phase are documented in the Software Requirement System (SRS). User interface design, detailed class diagrams, package diagrams, and multilayer sequence diagrams were designed during the system design stage and the last stage is implementation which is develop this project by using the android studio platform. This project has its own significance for the PPKJ residential. By using this system, it will help them to manage and records all the resident information, home away, issue of complaint and etc. The system also provides the notification function to inform the committee when resident issue the complaint. In fact, this proposed system will also enhance the efficiency of the residential of the business process by minimizing the danger of loss of data.